EDUKASI ENTERPRENEUR SYARIAH DAN BASIC KEUANGAN SYARIAH PADA SISWA MADRASAH ALIYAH TARBIYATUT THOLABAH LAMONGAN - Latifah, Eny; Abdullah, Rudi (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2023)
Knowledge related to entrepreneurship and sharia finance is important for students at the high school level to have as a form of education. The aim of this community service is to provide sharia entrepreneurial education and basic sharia finance for Madrasah Aliyah Tarbiyatut Tholabah Lamongan students. The community service method used is Participatory Action Research (PAR). There are 4 stages of service activities, namely: first, preliminary research by conducting outreach and observations with the target object of service, second, inculturation, namely by determining the theme and focus of service as well as determining the object of community service where Madrasah Aliyah Tarbiyatut Tholabah Lamongan is the target. Third, Action Action, namely by providing education through seminars for students to gain literacy about entrepreneurship and sharia finance. Fourth, evaluation is carried out in order to improve the quality of service in the future for a better process and has strong implications for community implementation.